2005
DOI: 10.1538/expanim.54.395
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Ophthalmic Diseases in 586 New Zealand White Rabbits

Abstract: The purpose of this study was to investigate spontaneous eye disease in New

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In 2005, Jeong reported spontaneous ocular anomalies in a series of 586 New Zealand White rabbits for laboratory use. 1.9% were affected by cataracts, 1.2% presented with choroidal hypoplasia, 0.2% were affected by persistent pupillary membrane and 0.3% with posterior synechiae . In 2011, Holve reported a survey of 1840 laboratory use rabbits (pigmented and albino) with an incidence of limited spontaneous vitreous lesion (0.3%) more prominent in cross‐NZ red strain (0.4%) in comparison with Dutch‐belted strain (0.2) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005, Jeong reported spontaneous ocular anomalies in a series of 586 New Zealand White rabbits for laboratory use. 1.9% were affected by cataracts, 1.2% presented with choroidal hypoplasia, 0.2% were affected by persistent pupillary membrane and 0.3% with posterior synechiae . In 2011, Holve reported a survey of 1840 laboratory use rabbits (pigmented and albino) with an incidence of limited spontaneous vitreous lesion (0.3%) more prominent in cross‐NZ red strain (0.4%) in comparison with Dutch‐belted strain (0.2) .…”
Section: Introductionmentioning
confidence: 99%
“…1.9% were affected by cataracts, 1.2% presented with choroidal hypoplasia, 0.2% were affected by persistent pupillary membrane and 0.3% with posterior synechiae. 6 In 2011, Holve reported a survey of 1840 laboratory use rabbits (pigmented and albino) with an incidence of limited spontaneous vitreous lesion (0.3%) more prominent in cross-NZ red strain (0.4%) in comparison with Dutch-belted strain (0.2). 7 However, the incidence of vitreous abnormalities was lower than that observed for corneal (5.7%) and lens abnormalities (3.6%).…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded, based on the above results, that spontaneous juvenile cataracts occurred in the rabbits and the incidences suggested an autosomal recessive model of inheritance. In a separate study to investigate spontaneous eye diseases in a group of 586 NZW rabbits, it was reported that unilateral or bilateral cataracts were identified in 1.9 percent of the rabbits and most of the affected rabbits were 2–4 months old . A recent retrospective study including 1022 NZW rabbits and 246 NZW × NZR F1 rabbits aged 6–16 weeks from five different suppliers demonstrated that the overall incidence of lenticular lesions were 4.6% in NZW rabbits and 3.3% in NZW × NZR F1 rabbits, which were similar to the incidence as previously reported .…”
Section: Introductionmentioning
confidence: 99%
“…Rabbits are presented to veterinarians mainly due to parasitic, dental, or infectious diseases and also because of ophthalmic disorders. An investigative study on 586 New Zealand White rabbits living in commercial breeding facilities revealed an incidence rate of 9.6% for ophthalmic diseases 1 . The predominant ophthalmic disease observed was blepharitis, followed by cataract and conjunctivitis.…”
Section: Introductionmentioning
confidence: 99%
“…So far, several studies have been published, concerning the microbiology and specific anatomy of the nasolacrimal duct of rabbits with dacryocystitis 1,2,4–13 . However, to the best of our knowledge, information on the clinical outcome of treated patients affected by this disease is scarce.…”
Section: Introductionmentioning
confidence: 99%